Design of Protection Relay Coordination Settings and Connecting to PLC Siemens S7-1500 For Load Shadding and HMI Display at PT. Semen Padang - Heru Dibyo Laksono; Mohamad Hanif Hakim; Rahman Ikhlas; Ridza Azri Ramlee (Andalas Journal of Electrical and Electronic Engineering Technology, 2022)
There are some vital loads and must not extinguished on the production activities of PT. Semen Padang cause the operational costs to rerun are very large. To solve this problem, it is necessary to evaluate the coordination settings of protection relays and automatic control systems to supporting the production process of PT. Semen Padang so production efficiency can be maintained. The relay settings to be evaluated are inverse time and instantaneous overcurrent relays by coordinating the main relay, backup relay 1 and backup relay 2 from downstream to upstream load feeder. The designed control system is an automatic load shedding and HMI display that can visualizing the system in realtime using the PLC Siemens S7-1500 with simulating on the PLCSimulator of the TIA Portal 15.1 software. Based on the calculations carried out, there are significant differences in the relay settings from the calculation results with the existing state. the relays installed in the system do not coordinate properly in the existing state, while after the calculation of the coordination relays the relays coordinate well. From the design of the control system, an automatic load shedding program and the display of the HMI system in real time were produced.